2007
DOI: 10.1111/j.1365-2265.2007.03119.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and body composition in preterm born children during prepubertal ages

Abstract: Premature born AGA and SGA children do not have insulin resistance when compared to term children if they have made a catch-up growth appropriate for their target height and have normal BMI. The similar insulin levels in preterm SGA and preterm AGA children together with increased insulin levels in term SGA children points to the fact that it is the intrauterine restriction in the third trimester that has an adverse effect on future adverse metabolic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 43 publications
7
53
1
Order By: Relevance
“…As has been shown in the previous report (20), insulin was significantly higher in term SGA children than in term AGA children (PZ0.003) and higher than in preterm SGA children (P!0.001). Preterm SGA and preterm AGA children had similar insulin levels.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…As has been shown in the previous report (20), insulin was significantly higher in term SGA children than in term AGA children (PZ0.003) and higher than in preterm SGA children (P!0.001). Preterm SGA and preterm AGA children had similar insulin levels.…”
Section: Resultssupporting
confidence: 66%
“…In fact, insulin level was one of the major determinants of ghrelin levels in our study. We, along with other investigators, have shown that SGA born children may have higher insulin levels in early childhood in spite of normal BMI levels (20,(26)(27)(28), and it has been shown that ghrelin has inverse correlation with insulin (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the offspring, low maternal vitamin B 12 status during pregnancy is associated with increased risk of neural tube defect, low lean mass and excess adiposity, increased insulin resistance, impaired neurodevelopment and altered risk of cancer (Rush et al 2014). In addition, children born with alteration of growth fetal development had a greater risk during adulthood of metabolic disorders and chronic illnesses (Darendeliler et al 2008). The current standard for prenatal care promotes preventive use of folic acid supplementation, but not the vitamin B 12 .…”
Section: Resultsmentioning
confidence: 99%